(3GdJfXje GdbGfhfj dGNJQGYGJ GdYGedjf (B: s (3OQGSI ebGQfI (B/ s - (3NGdO GdMQis; (3CMeO MSf GdHQYj (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2007)
(3JWQbfG ef NdGd gPg GdGWQhMI Gdi GdGMcGe GdYGeI dGNJQGYGJ GdYGedjf hMjK JfGhdfG GdTQhW GdeJWdHI ai gPG GdfhY ef GdGNJQGYGJ ShGA JYdb GdGeQ HEHQGe YbO GdYed Gh GdJhUd GdYGed Gdi GNJQGY (B: (3Ke GfJbdfG Gdi eYGdLI UhQ GNJQGYGJ GdYGedjf abSefGgG Gdi Ufajf GdUfa GdGhd GNJQGYGJ NOeI hGdJi jJhUd GdjgG GdYGed HJcdja ef UGMH GdYed hgPG GdUfa ef GdGNJQGYGJ jDhd Gdi UGMH GdYed HjfeG JfGhdfG ai GdUfa GdKGfi GNJQGYGJ NGQL GdNOeI hGdJi JTed fhYjf ef GdGNJQGYGJ hgi GdGNJQGYGJ GdYQVjI hGdGNJQGYGJ GdMQIs
(3jTJed Ydi edMb (B((3fehPL dJUQjM GNJQGYGJ GdYGedjf HaQfSG(B)s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2007.s
(3HHdjhLQGajG(B: (3UaMGJ(B284-288.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GNJQGYGJ GdYGedjf s; (3GdYGedjf GdeNJQYjfs; (3HQGAI GdGNJQGY s; (3UhQ GdGNJQGY s; (3GdTQhW GdehVhYjI ddGNJQGYs; (3GNJQGYGJ GdNOeIs; (3GdGNJQGYGJ NGQL GdNOeI s; (3GddLfI GdhWfjI dGNJQGYGJ GdYGedjf s; (3Mbhb hGdJRGeGJ GdYGeds; (3GdCSQGQ GdUfGYjIs; (3TQW YOe GdefGaSIs; (3GSJZdGd GdGNJQGY s; (3Mbhb UGMH GdYed Ydi GNJQGYGJ GdNOeI s; (3GNJQGYGJ GdYGedjfs; (3GdJfXje GdbGfhfis; (3YbO GdYeds; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2007